PENGARUH PENGAWASAN DAN MOTIVASI TERHADAP KEPUASAN KERJA PEGAWAI DI SMAN 1 TUKDANA INDRAMAYU - Nining Nurcahaya Ningsih; Nurjanah Rahayuningsih; Samsul Anwar (Jurnal Investasi, 2022)
ABSTRACT - The research is the result of research on the effect of supervision and motivation on employee job satisfaction at SMAN 1 TUKDANA. when needed. If employee job satisfaction is met it will increase employee motivation. The research method used by the researcher in this study is a qualitative research method. The data collection technique is in the form of employee research at SMAN 1 TUKDANA. Based on the expert opinion above, it can be synthesized that job satisfaction is basically something that is individual. In contrast, job satisfaction reflects a person's feelings towards his job. Based on the analysis and conclusions that: Teacher job satisfaction at SMAN 1 Tukdana Indramayu based on a questionnaire with 5 indicators, namely: Enjoying his job, loves his job, employee morale is 2.109 or 66.32% of respondents' responses to teacher employee job satisfaction are included in the Good category.